Raman spectroscopy of the laser irradiated titanium dioxide - Strelchuk, V.V; Budzulyak, S.I.; Budzulyak, I.M; Ilnytsyy, R.V.; Kotsyubynskyy, V.O.; Segin, M.Ya.; Yablon, L.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Evolution of anatase phase for the TiO₂ nanocrystals at their laser irradiation is researched by the method of combinational light dispersion. The observed changes of intensity, frequency and halfwidth of TiO₂ phonon lines are interpreted taking into account the effects of nonstoichiometry, superficial strains and phonon confinement. The found out parameter changes in the low frequency Eg mode show that laser irradiation results in substantial improvement of the structural ordering in the area of TiO₆ octahedrons bonds.